2020
DOI: 10.3389/fneur.2020.616764
|View full text |Cite
|
Sign up to set email alerts
|

Data-Driven, Visual Framework for the Characterization of Aphasias Across Stroke, Post-resective, and Neurodegenerative Disorders Over Time

Abstract: Aphasia classifications and specialized language batteries differ across the fields of neurodegenerative disorders and lesional brain injuries, resulting in difficult comparisons of language deficits across etiologies. In this study, we present a simplified framework, in which a widely-used aphasia battery captures clinical clusters across disease etiologies and provides a quantitative and visual method to characterize and track patients over time. The framework is used to evaluate populations representing thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…This pursuit is perfectly reasonable, provided there is sufficient intra-category homogeneity and inter-category separation that is reliably detected across studies, cohorts, and techniques. In clinical practice and across independent bodies of evidence, 8,12,32 however, graded performance variations within and between mutually exclusive categorisations are evident. Much of this variation is closely tied to individual differences in underlying neural degeneration, pathological processes, and disease progression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This pursuit is perfectly reasonable, provided there is sufficient intra-category homogeneity and inter-category separation that is reliably detected across studies, cohorts, and techniques. In clinical practice and across independent bodies of evidence, 8,12,32 however, graded performance variations within and between mutually exclusive categorisations are evident. Much of this variation is closely tied to individual differences in underlying neural degeneration, pathological processes, and disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27][28] Recent studies employing these methods in dementia syndromes demonstrate considerable success in explaining symptomatic heterogeneity in terms of coherent variations along orthogonal dimensions of clinical and cognitive changes. 8,12,[29][30][31][32] Across syndromes, such phenotypic variations further closely relate to unique patterns of neural network degeneration, 8,12,30 metabolic brain changes, 33 and categorically-distinct neuropathological drivers of underlying disease. 34 Applying transdiagnostic approaches in bvFTD and SD, therefore, holds immense promise in understanding clinical heterogeneity of these syndromes and associated neurocognitive mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A large-scale study of 330 participants with aphasia across three different aetiologies (post-stroke aphasia, primary progressive aphasia, and post-operative aphasia) found that severity was the primary dimension of variability, explaining 75% of the variance in aphasia battery sub-scores. 33 A more focused examination of 226 participants with post-stroke aphasia found that a ‘mild aphasia’ cluster was behaviourally and neuroanatomically distinct from the other two clusters, which corresponded to the semantic deficit and phonological deficit. 34 …”
Section: Introductionmentioning
confidence: 99%